2015
DOI: 10.1590/s1679-87592015091306302
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relationships among fish assemblages in a mudflat within Brazilian marine protected area

Abstract: Pessanha et al.: Trophic relationships of fish assemblages 135 Trophic relationships among fish assemblages in a mudflat within Brazilian marine protected areaThe present study on the temporal variations in diet and the trophic guilds of dominant fish species in a tidal mudflat, during the dry and rainy seasons. We aimed at classifying the diet composition of 17 species in the Mamanguape river estuary, northeastern Brazil, identifying the dominant food components and evaluating the effects of seasonality on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…Recent studies (Gning et al., ; Yeager, Layman, & Hammerschlag‐Peyer, ) have reported that consumption of food is important to the maintenance of physiological process in estuarine habitats, owing to the increased energetic costs of living at higher salinities. The plentiful food resources of the estuary facilitate its success across all estuarine zones (Campos, Silva, Sales, Oliveira, & Pessanha, ). Other resident species, such as gobies, were more abundant in the middle zone and their presence was closely associated with both the increased food resources (microphytobenthos) in this zone and the reduced predation risk provided by seagrass beds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Gning et al., ; Yeager, Layman, & Hammerschlag‐Peyer, ) have reported that consumption of food is important to the maintenance of physiological process in estuarine habitats, owing to the increased energetic costs of living at higher salinities. The plentiful food resources of the estuary facilitate its success across all estuarine zones (Campos, Silva, Sales, Oliveira, & Pessanha, ). Other resident species, such as gobies, were more abundant in the middle zone and their presence was closely associated with both the increased food resources (microphytobenthos) in this zone and the reduced predation risk provided by seagrass beds.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were mostly observed in abundant species and may indicate opportunistic feeding strategies (Selleslagh & Amara, 2015), according to changes in fauna composition along the saline gradient (Vivier et al, 2010;Selleslagh & Amara, 2015;Whitfield, 2015), ontogenetic changes during fish growth resulting in changes in lifestyle and consequently dietary changes (Luczkoviche et al, 1995), or between dry and rainy season, as noticed in Anchovia clupeoides, Bathygobius soporator, C. latus, E. argenteus and Sciades herzbergii (Campos et al, 2015).…”
Section: Fish Dietmentioning
confidence: 98%
“…Similar sample abundances or less were used by other studies to describe diet, trophic ecology or patterns of distribution in fish species (Nagelkerken & Van der Velde, 2004;Hammerschlag et al, 2010;Campos et al, 2015).…”
Section: Diet Analysismentioning
confidence: 99%
See 2 more Smart Citations